Modern Educational Approaches as a Factor of Development of Students’ Intellectual Abilities - Monkevičienė, Ona; Amirova, Amina; Ashirbayeva, Nazilya (Pedagogika, 2015)
Increased information flow requires introduction of such learning methods that enable to transfer a substantial scope of knowledge, provide high level of mastering sufficient volume enough material under study and its consolidation by the student in practice.